Multilevel Analysis: The Contextual Effect Village on The Risk Hypertension in Magelang, Central Java - Wawan Diyantana; Dono Indarto; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Hypertension affects one billion people worldwide. Death due to hypertension in the world is estimated at 9.4 million people every year. Factors related to lifestyle can increase the risk of hypertension. In addition, demographic and topographic factors of resi